Approximation of measurable periodic functions in measure by step functions - Pichugov, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
For spaces defined by a function $ϕ$ of the type of modulus of continuity, we prove direct and inverse Jackson theorems for the approximation by step functions with uniform partition.